A novel fiber optic system to map dissolved oxygen concentrations continuously within submerged sediments. Issue 3 (3rd July 2019) - Jeffery Reeder, W.; Quick, Annika M.; Farrell, Tiffany B.; Benner, Shawn G.; Feris, Kevin P.; Basham, William J. R.; Marzadri, Alessandra; Tonina, Daniele; Huber, Christian
Abstract : Dissolved oxygen (DO) concentration is a primary indicator of redox and biogeochemical activity in the hyporheic zone (HZ) of fluvial systems. Due to the inherent difficulty of measuring chemical concentrations in hyporheic sediments, field measurements are typically spatially and temporally sparse. Consequently, conceptualizations of biogeochemical processes within streambed sediment have not been validated but only supported by temporally and spatially sparse observations. To overcome these limitations and provide spatially and temporally high-resolution measurements, we developed a multi-point, in situ DO measurement method based on a multiplexed optical network. This system was deployed in a large-scale flume and a cobble-bed headwater stream. In both settings, pore-water DO concentrations were measured at unprecedented spatial and temporal resolution. Our findings demonstrate the value of high-density DO measurements. These measurements are used to illuminate some shortcomings in the current conceptualization of reactive solute transport in the HZ.